Book Publishing Business in Romania – An Analysis from the Perspective of Porter's Five Force Model - Ana-Maria GRIGORE (Revista de Management Comparat International)
The book publishing industry is facing numerous challenges and opportunities resulting from various fundamental forces. An understanding of the forces that are shaping and shifting the competitive landscape is useful not only in understanding the strategic positioning decisions of the firms in this industry, but also in understanding the dramatic structural changes that are currently occurring in the publishing production and distribution sector. We frame this discussion using the analytical concepts of value chains and Porter’s Five Forces.